Corrosion protection by octadecylphosphonic acid in flow conditions - Kristan Mioč, Ekatarina; Otmačić Ćurković, Helena (2019)
The aim of this work was to examine the influence of the flow rate of corrosive media on the stability of self-assembled films of octadecylphosphonic acid on copper-nickel alloy and stainless steel. The studies were conducted in river and seawater in a laboratory scale flow system. Corrosion behaviour of protected and unprotected alloys was examined by electrochemical techniques, electrochemical impedance spectroscopy, and polarization measurements. The results show that octadecylphosphonic acid films can efficiently protect copper-nickel and stainless steel from corrosion in flowing natural waters. The flow of corrosive media had the highest influence on the stability of films on CuNi in seawater, while in all other studied cases, the protective properties of ODPA film changed insignificantly with the change of the flow rate.
Bibliografija: 24 jed.
Summary.
Keywords: Zaštita od korozije -- Fosfonske kiseline -- Oktadecilfosfonska kiselina -- Slitine -- Legure -- Nehrđajući čelik -- Morska voda -- Riječna voda -- Protok vode -- Brzina protoka